Ação trófica de aditivos fitogênicos, glutamina e ácido glutâmico sobre a Bursa de Fabrícius e intestino delgado de frangos de corte - Pelícia, Vanessa Cristina [UNESP]; Ducatti, Carlos [UNESP]; de Araujo, Priscila Cavalca [UNESP]; Stradiotti, Ana Cristina [UNESP]; Aoyagi, Monica Megumi [UNESP]; Fernandes, Barbara da Silva [UNESP]; Silva, Evandro Tadeu [UNESP]; Sartori, José Roberto [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this study was to evaluate the effect of phytogenic additives and glutamine plus glutamic acid, associated or not, on histomorphometry of bursa of Fabricius and small intestine, oocyst count and lesion scores, and carbon turnover of duodenal mucosa of broiler chickens infected with Eimeria acervulina. A total of 450 male broiler chickens was distributed into a completely randomized design with six treatments and three replications. Treatments consisted of control diet (CD); CD + coccidiosis vaccine; CD + antibiotic performance enhancers and anticoccidial (APE/AC); CD + glutamine and glutamic acid (Gln/Glu); CD + phytogenic additives (PA); CD + Gln/Glu + PA. Birds on treatment CD + vaccine were vaccinated via drinking water at three days of age against coccidiosis. At 16 days of age all birds of all treatments were inoculated orally and individually with 500,000 oocysts of Eimeria acervulina. There was no treatment effect on lesion score in the intestinal epithelium of birds. The smaller number of excreted oocysts was observed in groups of birds fed diets containing APE/AC and PA. Were observed better results of villus height and crypt depth for duodenum and ileum of birds of treatments containing Gln/Glu at 7 days of age, and Gln/Glu and PA at 21 days of age. Higher percentage of cortical area from bursa follicles was observed in birds fed diets supplemented with Gln/Glu and PA at 7, 14 and 21 days of age. Increased turnover of intestinal mucosa was observed in treatments containing Gln/ Glu, indicating acceleration in development and regeneration of damaged tissue. Glutamine plus glutamic acid and phytogenic additives can provide improvements to structure, and thus to intestinal function, as well as to better immune response against the infectious challenges. Phytogenic additives can be used for coccidiosis control of broiler chickens where the use of antibiotic performance enhancers and anticoccidials is prohibited.
Trophic action of phytogenic additives, glutamine and glutamic acid on Bursa Fabricii and small intestine of broilers
Keywords: Bursa Fabricii; Coccidiosis; Glutamic acid; Glutamine; Lesion score; Small intestine; Stable isotope; Turnover